An Economic Assessment of Farmer Adaptation to Climate Change Using Innovation in Sweet Potato Technologies in Uganda - Ilukor, J. (Makerere University, 2010)
Sweet potato technologies, like drought resistant varieties and virus cleaned planting material have shown resilience of agricultural systems to climate change related effects. However, adoption of these technologies is very low in Uganda. This study was designed to assess the adoption potential (economic feasibility) of these technologies by rural farm household under climate change conditions. Data were collected from study areas in Kabale and Soroti districts using household survey, focused group discussion and secondary sources. The Tradeoff Analysis, Minimum Data Model Approach (TOA-MD) was employed to estimate the adoption potential of alternative practices under climate change. Results from focused group discussion reveal that farmers have developed different adaptation strategies to climate change such as swamp reclamation, migration to other areas, mixed cropping among others. Access to these technologies was limited and government provision of planting material usually ends up with a few privileged farmers. Results from the model also show that, adoption potential under climate change is high and varies depending on agro-ecological zones, wealth status and opportunity costs of adopting the technology. However, providing free planting material is not feasible and if undertaken, it does not benefit the poor but the rich. We conclude that, adoption of these technologies is economically feasible and recommend that, climate change adaptation policy should target the poor, institutional framework and systems should be strengthen to improve on accountability in the implementation of climate change adaptation strategies of public nature. Measures are also needed to raise returns and reduce the opportunity costs of climate change adaptation strategies. Further research is needed to explore joint adoption of crop technologies that have show resilience to climate related effects.